Association between non-penetrative sexual activities and depression in women with vaginismus: a cross-sectional study - Yavuzkir, Seyda; Aslan, Melike; Yurt, Nurdan; Baykara, Sema (Sage Publications Ltd, 2024)
Objective This cross-sectional study aimed to explore the association between non-penetrative sexual activities (NPSA) and depression levels in women diagnosed with vaginismus.Methods A cross-sectional retrospective study was conducted between March 2016 and June 2019, after approval by the F & imath;rat University Faculty of Medicine ethics committee. Participants comprised married women referred to our female sexual dysfunction outpatient clinic with vaginismus. Diagnosis of vaginismus was established following comprehensive evaluations, including gynecological examination and psychiatric assessment. Sociodemographic data and Beck Depression Inventory (BDI) scores were collected. We compared depression levels between women who engaged in NPSA and those who did not.Results Of the 75 women with primary vaginismus included in the study, 18 did not engage in any NPSA and 57 engaged in at least one NPSA. The average BDI score of those who engaged in NPSA was significantly lower than those who did not. A negative correlation was found between the number of NPSA engaged in and BDI scores (r = -0.494).Conclusions Women with vaginismus had high depression scores, but engaging in NPSA was associated with lower depression levels. The findings suggest that incorporating NPSA into clinical interventions may be beneficial for managing depression in women with vaginismus.
Keywords: Depression; vaginismus; non-penetrative sexual activity; female sexual dysfunction; genito-pelvic pain/penetration; cross-sectional study; retrospective